Pricing the ECB's forward guidance with the EONIA swap curve. (27th February 2017) - Picault, Matthieu
Abstract: On July 4, 2013, following several other major central banks, the European Central Bank (ECB) gave for the first time forward guidance on interest rates, which affected market participants' expectations of future interest rates in the context of a Zero Lower Bound. Using an ARMAX(1, 1) model in which the effect of the communication of negative macroeconomic news was disentangled from the commitment positive shock, the impact of the forward guidance on money market interest rates is estimated through the Euro Overnight Index Average swap, also called overnight index swap, at maturities between 2 months and 10 years using abnormal returns from an event study. The results and robustness checks suggest that the ECB's guidance lowered overnight index swap rates for maturities within 10 months to 3 years. These results imply the existence of a commitment effect from the ECB's communication. In the context of decreasing market liquidity because of the 3‐year long‐term refinancing operation repayment, market participants priced the low period of interest rates until mid‐2016.